Gendered Subjectivities in English Classrooms: A Critically Queered Examination of Sex-Segregated Education - Javier Sierra-Gordillo (Universidad Nacional de Colombia, 2024)
This study explores the link between gender and language in single-sex schools in Colombia. Using feminist theory, the study analyzes the gendered subjectivities of English-as-a-foreign-language learners in a private school in Bogotá. It examines how heterosexuality is forced upon learners and how their subjectivities are impacted by the heteronormative discourse surrounding sex-gender learning differences. The study utilizes conversation analysis and speech act theory to examine data. The findings reveal that gendered subjectivity is complex and constitutes an ongoing struggle. There is a need for further research on gender and English teaching in educational settings, emphasizing the importance of studying sociolinguistic power relationships.